The Role of Local Communities in Waste Management at Tukad Bindu Tourist Destination in Denpasar Bali - Satia Negara, I Made Weda; Sedana Putra, Anak Agung Ngurah; Sumardani, Rizki (Jurnal Manajemen Pelayanan Hotel, 2024)
Tukad Bindu is a tourism area faced with the problem of increasing waste generation due to the increase inpopulation and human activity. Waste production increases every day along with the increase in populationand community consumption patterns. The thing that must be done to overcome the increasing volume ofwaste is to reduce the volume of waste from its source through empowering community participation. Theproblem in community participation regarding waste management is what form of regulation related to wastemanagement in Tukad Bindu Neighbourhood, Denpasar Bali. The introduction of waste management to thecommunity aims to introduce how to manage waste in preserving and maintaining environmental cleanlinessin Tukad Bindu Bali.Based on the results of the research, one form of community participation in environmental improvementefforts is by contributing labour in the form of community service and participating in waste management. Inaddition, they also hold community meetings, which are attended by some residents for the kelurahan level.The community carries out these activities without feeling forced at all. The level of community participationthat occurs in the Tukad Bindu Neighbourhood is according to the moderate category, the communityparticipates in waste management but tshe implementation is still not optimal. The important role of thecommunity and all parties is expected for the realisation of success in providing community participationlearning in waste management to maintain cleanliness in the Tukad Bindu neighbourhood, Denpasar Bali.Keywords: The Role of Local Communities, Waste Management. Tukad Bindu Bali